2022
DOI: 10.1111/joca.12500
|View full text |Cite
|
Sign up to set email alerts
|

Health insurance coverage during the COVID‐19 pandemic: The role of Medicaid expansion

Abstract: Using data from the US Census Bureau's Household Pulse Survey, we analyzed the likelihood of loss of health insurance and enrollment into new health coverage during the early months of the COVID‐19 pandemic. Loss of employment was associated with a significant increase in the likelihood of loss of health insurance and, specifically, an increase in the likelihood of employer‐sponsored health insurance. However, individuals in Medicaid expansion states experienced a lower likelihood of loss of health insurance c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The pandemic resulted in many patients losing their jobs, income, and insurance benefits. 16,17 This could have contributed to affordability issues resulting in more referrals to pharmacists to identify cost-effective medication regimens for patients. The stability in the percentage of COAT visits completed implied a continued need for opioid taper services throughout the study.…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic resulted in many patients losing their jobs, income, and insurance benefits. 16,17 This could have contributed to affordability issues resulting in more referrals to pharmacists to identify cost-effective medication regimens for patients. The stability in the percentage of COAT visits completed implied a continued need for opioid taper services throughout the study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis revealed poor health outcomes and higher mortality rates related to malignancies in patients with a lack of healthcare coverage [20]. Types of healthcare coverage were also shown to impact infection rates and mortality outcomes due to COVID-19 based on comparison of Medicaid expansion and nonexpansion states [21]. Searching for healthcare providers that fall within a new healthcare coverage plan may be difficult.…”
Section: Plos Onementioning
confidence: 99%